What is special about special? - Greenberg, Yael; Zeijlstra, Hedde (Proceedings of the Amsterdam Colloquium, 2024)
This paper concerns the semantics of the adjective special as in This is a special book about Stalingrad. To the best of our knowledge no discussion of the semantics of special exists in the current literature. There is, however, some research on (a)typical which takes it to be a subsective, multidimensional and intensional adjective, involving comparison to stereotypes. We first hypothesize that special could be modeled as an antonym of typical, i.e. as atypical. We observe, however, that there are distributional and interpretational differences between atypical and special, and propose to capture them by taking special to involve non-stereotypical properties which hold of the individuals in question in the speaker’s / protagonist’s teleologically / bouletically accessible worlds.